The negative effects of the Internet in sex education: An Empirical Study on third-secondary students in Buraydah - Al-Turki, Huda Ibrahim (Journal of Humanities & Social Sciences, 2022)
The study, with key findings and recommendation in its scientific nature, aims at defining the sides of the negative social impacts of internet on the Sexual Education of the girls in respect of the sexual information on males and females, sexual diseases, natural and medical sexual stimulants and information related to Aesthetic Education.The study's adopted the descriptive method in research. Its tool is questionnaire and Sample number is 100 female students.Adopting the afore-mentioned methodical procedures in this study,I came to two key findings which are as follows:Due to obtaining information on the Aesthetic Education, the girls, more likely in their adolescence stage tend to the internet but in medium rates. The study found that the internet provides girls with sexual information, on man, women, love and mates, that may disagree with the socio-local culture, whether she browses and watches pornographic websites contain liberal images and words or reviews scientific websites based on sexual provocation especially in the case when she is not followed up or directed by family.The girl in high rates, tends to the internet for both to search for enjoyment and excitement, not learning or to obtain information relates to Aesthetic Education related to hygiene, fitness, nutrition and sport. The study found that the internet provides the girl with information on Aesthetic Education that may disagree with our culture.The study hence recommends that religious and moral values should be instilled in girls by parents, teachers and educators, and that they should be given skills that will enable them to maintain cultural identity.
Keywords: sex education; sexual information; Aesthetic education